Flock-fishing deep-diving piscivores (Great Crested Grebe Podiceps cristatus, Great Cormorant Phalacrocorax carbo, Common Merganser Mergus merganser) at Lake Vombsjön, southern Sweden, and those that exploit them - Källander, Hans (Ornis Svecica, 2018)
Lake Vombsjön in southern Sweden is visited by large numbers of Great Crested Grebes Podiceps cristatus (>2000), Great Cormorants Phalacrocorax carbo (sometimes >1000) and Common Mergansers Mergus merganser (up to 2000) in late autumn and early winter. Different species exploit them. Great Crested Grebes are used especially by commensal Common Gulls Larus canus; the gulls take advantage of fish that flee towards the surface. Common Gulls also use cormorants and mergansers in the same way but also try to kleptoparasitize them. Both Herring Gulls Larus argentatus and Great Black-backed Gulls Larus marinus kleptoparasitize these two species, while Red Kites Milvus milvus, Grey Herons Ardea cinerea and Carrion Crows Corvus corone use them commensally. White-tailed Eagles Haliaeetus albicilla seem to use both methods to obtain fish. On 50% of one hundred visits during November to March, eagles were seen flying low over the fishing flocks. They would fly a metre or so above the flocks and then accelerate and attack a bird holding a fish. The bird would then either try to escape by a rush or by diving, dropping the fish which the eagle seized. Interestingly, the flock-fishing birds showed no fear reactions towards the eagles but appeared to regard them similarly to large gulls.